Beginning Drupal 7 - Tomlinson, Todd.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
This book focuses on the nontechnical user who is responsible for building, maintaining, and managing Drupal web sites. The book covers why you should consider using Drupal when building a new web site, what Drupal is, installing and configuring Drupal, creating and managing content, managing users, adding functionality to your web site through Drupal modules, and more advanced topics on using themes, panels, and views. By reading this book, you will: Understand why you should use Drupal and the power of the platform. Quickly build confidence in your ability to use Drupal. Gain the knowledge necessary to build, deploy, and manage web sites of moderate complexity on Drupal 7.
to Drupal -- Creating and Managing Content -- Creating and Managing Users -- Taxonomy -- Creating Menus -- Installing Themes -- Drupal Blocks -- Drupal Modules -- Enabling Interactive Capabilities -- Content Types -- Views -- Panels -- Theming -- Administering Your Drupal Site -- Putting It All Together -- Case Study.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems